1992
DOI: 10.1002/j.2048-7940.1992.tb01559.x
|View full text |Cite
|
Sign up to set email alerts
|

The Foot at Risk: Identification and Prevention of Skin Breakdown

Abstract: This article presents the major predisposing factors and measures associated with preventing nosocomial foot lesions. The combination of nursing interventions and the appropriate use of protective devices can markedly reduce the incidence of foot lesions acquired in the hospital. Patient and family education is another important aspect in preventing skin breakdown of the foot at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The slowness of the healing process predisposes to infectious complications. In a review in the United States, it is reported that the presence of an ulcer for more than one month without healing can evolve to an infection or ischemia, or even both (29) .…”
Section: Discussionmentioning
confidence: 99%
“…The slowness of the healing process predisposes to infectious complications. In a review in the United States, it is reported that the presence of an ulcer for more than one month without healing can evolve to an infection or ischemia, or even both (29) .…”
Section: Discussionmentioning
confidence: 99%
“…During a thorough nursing assessment, the rehabilitation nurse will identify other risk factors associated with the development of chronic wounds. Extreme changes in weight (Friebel, 1993), altered nutritional status (AHCPR, 1992;Basta, 1994;Hanson et al, 1993;Schultz, 1993) and dehydration (Basta, 1994), circulatory impairment (Friebel, 1993;Yetzer & Sullivan, 1992), sedating medications (Yetzer & Sullivan, 1992), infection, diabetes mellitus, age, depression (Dittmar, 1989), poor hygiene, drug or alcohol use, smoking (Basta, 1994;Hanson et al, 1993), and very dry (Hanson et al, 1993) or very moist skin are some of the predisposing factors for wound development.…”
Section: Rehabilitation Clients At Risk Of Wound Developmentmentioning
confidence: 99%
“…As a core member of the interdisciplinary team, the rehabilitation nurse collaborates with the physical therapist and the occupational therapist (Neal, 1995b) in choosing the appropriate durable medical equipment, such as wheelchair cushions and bed mattresses (Dittmar, 1989;Friebel, 1993;Jester & Weaver, 1990;Yetzer & Sullivan, 1992). An overhead trapeze, if the client has the strength to use it, can be very helpful for preventing shearing.…”
Section: The Role Of the Rehabilitation Nursementioning
confidence: 99%
See 1 more Smart Citation
“…Yetzer et al (1992) referem que as áreas dos pés com tendência para lesões são o hálux, a superfície plantar na região dos metatarsos, as laterais externas do pé, os calcâneos e os maléolos, confirmando assim algumas áreas em nosso estudo.…”
unclassified